(untitled) (Advances in Applied Mathematics and Mechanics, 2018)
The boundary particle method (BPM) is a truly boundary-only collocation scheme, whose basis function is the high-order nonsingular general solution or singular fundamental solution, based on the recursive composite multiple reciprocity method (RC-MRM). The RC-MRM employs the high-order composite differential operator to solve a much wider variety of inhomogeneous problems with boundary-only collocation nodes while significantly reducing computational cost via a recursive algorithm. In this study, we simulate the Kirchhoff plate bending problems by the BPM based on the RC-MRM. Numerical results show that this approach produces accurate solutions of plates subjected to various loadings with boundary-only discretization.